THE ROLE AND RELEVANCE OF FOREIGN LANGUAGES IN THE EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Fayzullayeva Nodira (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This article highlights the role of foreign languages in the education system of the Republic of Uzbekistan, their strategic importance, the reforms being implemented within  the  framework  of  state  policy,  modern  methodological  approaches,  the international and national certification system, measures aimed at training competitive personnel,  and  integration  processes  in  international  cooperation.  Furthermore,  it substantiates that in the developing education system of the Republic of Uzbekistan, learning  foreign  languages  is  not  only  a  necessity  but  also  a  vital  foundation  for progress.